2020
DOI: 10.1177/2516602620937878
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and BAME Group in the United Kingdom

Abstract: COVID-19 is known to disproportionately affect ethnic minorities in number of settings. This phenomenon has also been reported in the UK where the black, Asian and minority ethnic (BAME) group has adverse health outcomes in terms of number of both cases and mortality rates when compared to the white local population. This trend is also observed among the BAME staff working in the National Health Service. Number of plausible explanations and the importance of various approaches including social-determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…For reasons that are not completely clear, non‐white individuals are between two and three times more likely to die from COVID (Bhatia, 2020). A higher proportion of all deaths among nurses has to date been reported in black, Asian and minority ethic (BAME) nurses (Braithwaite, 2020).…”
mentioning
confidence: 99%
“…For reasons that are not completely clear, non‐white individuals are between two and three times more likely to die from COVID (Bhatia, 2020). A higher proportion of all deaths among nurses has to date been reported in black, Asian and minority ethic (BAME) nurses (Braithwaite, 2020).…”
mentioning
confidence: 99%
“…Hence, it is concerning that lockdown restrictions could potentially exacerbate this group’s vulnerability due to further reductions in PA in an already inactive group. Another group, evidenced to be at higher risk from COVID-19 are those from BAME populations [21,22]. Again, we found a stark contrast in PA levels, in terms of reduced step-count, in those from BAME groups compared to those identifying as White British.…”
Section: Discussionmentioning
confidence: 50%
“…Analysis of deaths and hospital admissions also revealed that there were disproportionately high numbers among BAME populations. While this may indeed partly have a genetic cause, it also highlighted pre-existing issues of social inequality and unequal access to healthcare and a safe working environment (Bhatia, 2020).…”
Section: Covid-19: Shared Vulnerability But Unequal Resiliencementioning
confidence: 99%